Nasopharyngeal Airway Insertion - Thomas A. Nicholas; Ben H. Boedeker; Nick Markin; Huiling Pang (Association of American Medical Colleges, 2011)
Abstract This module was developed to teach learners how to place a nasopharyngeal airway. It was developed using original illustrations, text notes based on recent literature research with citations, live operating room patient interaction video from patients undergoing anesthesia and surgery, and original audio narration. The module was constructed to allow for web-based virtual training or independent study, and was intended to augment other airway management modules which already exist or our web site at the Center for Advanced Technology and Telemedicine at the University of Nebraska Medical Center. The modules are being utilized by our medical students, residents, and respiratory therapists for primary and secondary training. The module functions similar to a PowerPoint presentation by allowing the user to scroll through slides or simply observe the module as a self-playing presentation. It takes approximately 20 minutes to complete when in self-playing mode. This teaching module has been deployed on our web site allowing multiple providers to access the module and utilize it in the education of health care provider learning airway management.